Multimedia Based Immune System And Skin Health Education As A Learning Innovation - Hartanto, Deddy; Ratnasari, Diana Tri (LPPM Universitas Bina Bangsa, 2026)
Health education in higher education requires innovative approaches to ensure students understand complex and abstract material optimally. The immune system and skin health are essential components of medical education, but are often delivered through conventional methods that do not support conceptual understanding. This study aims to determine the effect of multimedia-based immune system and skin health education as a learning innovation on students' understanding of the Faculty of Medicine, Wijaya Kusuma University, Surabaya. The study used a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The subjects consisted of two classes of students: an experimental class that received learning using Canva-based multimedia and a control class that received conventional learning. Data collection was conducted through pre-tests and post-tests to measure improvements in student understanding. The results showed that the initial abilities of both classes were relatively comparable. After treatment, the experimental class showed a higher increase in learning outcomes compared to the control class. This indicates that the use of multimedia learning has a positive impact on student understanding. Canva-based multimedia is able to present material visually, systematically, and attractively, helping students understand the concepts of the immune system and skin health more effectively. Thus, multimedia-based immune system and skin health education can be used as a relevant and applicable learning innovation to support improving the quality of health learning in higher education.